TVET teacher education: a vision beyond tradition - Knight, J. A. (Penerbit UTHM, 2009)
This paper identifies some basic information about brain based learning, which includes some technical information presented in terms that all may understand. Two major psychological notions, which underpin all we know about the teaching and learning process, will be identified and described. Further, this paper will focus upon best practice strategies that have been identified in the research on student achievement and will provide specific suggestions on how to implement them. It will demonstrate why the vocational education model is the premier educational delivery system for all of education and will aid in the developing of a vision beyond tradition.